Longitudinal imaging of the availability of dopamine transporter and D2 receptor in rat striatum following mild ischemia. Issue 2 (February 2017) - Momosaki, Sotaro; Ito, Miwa; Yamato, Hiroko; Iimori, Hitoshi; Sumiyoshi, Hirokazu; Morimoto, Kenji; Imamoto, Natsumi; Watabe, Tadashi; Shimosegawa, Eku; Hatazawa, Jun; Abe, Kohji
The changes in the availability of striatal dopamine transporter and dopamine D2 receptor after mild focal ischemia in rats were measured using a small animal positron emission tomography system. Mild focal ischemia was induced by 20-minute middle cerebral artery occlusion. [ 11 C]PE2I binding to dopamine transporter was transiently increased on the ipsilateral side of the striatum at 2 days after middle cerebral artery occlusion. On day 7 and 14 after middle cerebral artery occlusion, [ 11 C]PE2I binding levels were decreased. In contrast, [ 11 C]raclopride binding to dopamine D2 receptor in the ipsilateral striatum had not changed at 2 days after middle cerebral artery occlusion. [ 11 C]Raclopride binding was significantly decreased on the ischemic side of the striatum at 7 and 14 days after middle cerebral artery occlusion. Moreover, on day 1 and 2 after middle cerebral artery occlusion, significant circling behavior to the contralateral direction was induced by amphetamine challenge. This behavior disappeared at 7 days after middle cerebral artery occlusion. At 14 days, circling behavior to the ipsilateral direction (middle cerebral artery occlusion side) was significantly increased, and that to the contralateral direction also appeared again. The present study suggested that amphetamine-induced circling behavior indicated striatal dopaminergic alterations and that dopamine transporter and dopamine D2 receptor binding could be key markers for predicting motor dysfunction after mild focal ischemia.